Faktor Yang Mendorong Mahasiswa Prodi Manajemen Untuk Berwirausaha Dalam Lingkungan Universitas Winaya Mukti - Nurul Adha, Anisa; Ayu, Sri (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2023)
Young entrepreneurship in the campus environment has become an increasingly significant phenomenon in fostering an entrepreneurial spirit among students, especially in the Management Study Program. This research aims to describe the dynamics and factors that encourage Management Study Program students to become involved in entrepreneurial activities. This study involved surveys and interviews with Management Study Program students at various study levels on the UNWIM Campus. In the early stages, the results show an increase in student interest and participation in entrepreneurial activities, both in forming startups and developing small business projects. Factors identified as the main drivers include entrepreneurship education integrated into the curriculum, institutional support involving lecturers and staff, and inspiration from success stories from Management Study Program alumni. Additionally, the importance of an entrepreneurial mentality and engagement in training that enriches business skills also plays a key role. The results of this research provide a significant contribution to understanding how the campus environment, especially the Management Study Program at UNWIM, can be a catalyst for developing an entrepreneurial spirit among students. The implications of these findings can help develop more effective policies and educational programs to encourage young entrepreneurs in the campus environment.